2013
DOI: 10.7448/ias.16.1.17325
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and risk factors associated with a pruritic papular eruption in people living with HIV in India

Abstract: IntroductionPapulopruritic eruption (PPE) occurs in people living with HIV in India. Understanding the risk factors associated with this disease may help decrease the prevalence of PPE.MethodsThis study was a case-control study performed at the Government Hospital of Thoracic Medicine, a tertiary care hospital in Chennai, India. Cases included HIV-positive, antiretroviral (ARV) therapy-naïve adults experiencing a pruritic skin eruption for longer than one month, with evidence of multiple papular or nodular les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This was comparable to a study done in Uganda where the mean age of participants was noted to be 35±8 years [18]. A study in India reported that the mean age of the PPE patients was 34.2±7.5 years [19]. Most of the patients with PPE in this study (68.8%) were less than 45 years old, in keeping with the age group more likely to be HIV infected as reported in similar studies in our environment [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…This was comparable to a study done in Uganda where the mean age of participants was noted to be 35±8 years [18]. A study in India reported that the mean age of the PPE patients was 34.2±7.5 years [19]. Most of the patients with PPE in this study (68.8%) were less than 45 years old, in keeping with the age group more likely to be HIV infected as reported in similar studies in our environment [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…1,15 Patients with dermatological manifestations that are associated with pruritus may have decreased CD4 þ T-cell counts. 7,16 In this study, participants with chronic pruritus had a mean CD4 þ T-cell count of 488 AE 222 cells/mL (range 26e1536). No significant association was found between pruritus and CD4 þ T-cell count similar to other reports.…”
Section: Commentmentioning
confidence: 91%
“…The incidence of papulo-pruritic eruption of HIV varies between 12% and 46% depending on the geographic location. 16 PPE presents as extremely pruritic, symmetric, skin-coloured to erythematous papules and pustules. Excoriations are common due to intense pruritus (Figure 9).…”
Section: Papulo-pruritic Eruption (Ppe)mentioning
confidence: 99%